Zinc Phosphate Nanoparticles Preparation and Their Antimicrobial Activity - Kopel, Pavel; Cernei, Natalia Vladimirovna; Gagić, Milica; Horký, Pavel; Šmerková, Kristýna; Adam, Vojtěch (Tanger, 2019)
Zinc phosphate particles were prepared by reaction of zinc nitrate with hydrogen phosphate, diphosphate and triphosphate, and characterized by Dynamic Light scattering (DLS) and Scanning Electron Microscopy (SEM). Antibacterial effect of ZnO nanoparticles and zinc phosphates ones were compared. Bacterial strains of (Escherichia coli NCTC 13216, Staphylococcus aureus NCTC 8511, and Methicillin-resistant S. aureus CCM 7110 were used for the testing. Oxidative stress was determined the GSH/GSSG ratio by using Highpressure liquid chromatography with twelve-channel CoulArray electrochemical detector (HPLC-ED). It has been demonstrated the zinc phosphate particles shown better antibacterial properties and smaller toxicity, than the conventional ZnO.

Zinc phosphate particles were prepared by reaction of zinc nitrate with hydrogen phosphate, diphosphate and triphosphate, and characterized by Dynamic Light scattering (DLS) and Scanning Electron Microscopy (SEM). Antibacterial effect of ZnO nanoparticles and zinc phosphates ones were compared. Bacterial strains of (Escherichia coli NCTC 13216, Staphylococcus aureus NCTC 8511, and Methicillin-resistant S. aureus CCM 7110 were used for the testing. Oxidative stress was determined the GSH/GSSG ratio by using Highpressure liquid chromatography with twelve-channel CoulArray electrochemical detector (HPLC-ED). It has been demonstrated the zinc phosphate particles shown better antibacterial properties and smaller toxicity, than the conventional ZnO.
Zinc Phosphate Nanoparticles Preparation and Their Antimicrobial Activity
Keywords: Zinc phosphate; Zinc oxide; Antimicrobial properties; Zinc phosphate; Zinc oxide; Antimicrobial properties